Qualidade do sono em mulheres com disfunções do trato urinário inferior - Albanezi, Daniele Furtado (Universidade Federal de São Carlos, 2016)
Climacteric women have considerable prevalence of both disorders of the pelvic floor, such as urinary incontinence (UI) and nocturia, as sleep disorders, which can compromise the quality of life and sleep. Therefore, this thesis aims to: (1) compare the sleep of quality women's with and without UI and correlate the sleep of quality with the quality of life of women; (2) determine the effects of treatment with electrical stimulation of the tibial nerve (ENT) on the sleep of quality in women with nocturia. The two studies used to evaluate the slee´of quality the Pittsburgh Sleep Quality Index (PSQI), the King's Health Questionnaire (KHQ) to assess quality of life in addition to these two tools, the study (2) used the Scale Epworth sleepiness to assess daytime sleepiness and by vaginal palpation and perineometer evaluated the pelvic floor muscles before and after treatments. For the study (1) were evaluated 60 women incontinence (UI stress-SUI, urgency incontinence-IUU or mixed IU-IUM) and continents, while for the study (2) were evaluated 40 women with nocturia allocated for the two types of proposed treatments, one group received ENT (GENT) and another group received training of the pelvic floor muscles + behavioral therapy (GTMAP + CT) for 12 weeks with a weekly service. Given the results presented in the study (1), it can be observed that women with UUI and MUI had worse overall PSQI score and worst sleep area and provision of KHQ, compared to women with SUI also IUM was related to worst score of areas: limitation of activities of daily living (compared to SUI), physical limitations (compared to SUI and UUI), personal relationships (compared to UUI). Both women continents as those presented IUU had worse habitual sleep efficiency, compared to those with SUI. Nocturia showed moderate positive correlation with sleep area and provision of KHQ and the total PSQI score in women with UI. After the two treatments proposed in the study (2) was observed improvement in quality according to the domains of PSQI sleep: subjective sleep quality, latency, sleep duration, total score. Moreover, 35% of them now have no more nocturia, indicating that both techniques are effective to reduce the number of awakenings during the night to urinate. The improvement in daytime sleepiness was observed in GTMAP + CT, and daytime dysfunction (PSQI) in GENT. Regarding quality of life, both groups improved in the KHQ domains: AVD limitation, emotions, sleep and mood and severity measures; the GTMAP + CT showed a significant improvement in UI impact area compared to GENT. Faced with the above results, it is concluded that women with MUI and UUI have worse sleep quality and life than women with SUI, and that with the treatment of ENT or TMAP + CT can improve the sleep of quality and quality of life women with nocturia.
Keywords: Transtornos do sono-vigília; Climatério; Incontinência urinária; Noctúria; Sleep wake disorders; Climateric; Urinary incontinence; Urge; Nocturia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL